The use of eye-tracking methods for evaluation of responsive web application - Meksuła, Dariusz; Mikołajczyk, Konrad; Plechawska-Wójcik, Małgorzata; Borys, Magdalena (Journal of Computer Sciences Institute, 2018)
The purpose of this article is to present the eye-tracking method in the context of evaluation of responsive web application dedicated to manage students practices. To determine usability of the application the eye-tracking method has been chosen due to its high objectivity. Using this method one can unequivocally determine the user gaze direction, which interface elements enchained his attention and which ones were completely skipped. As part of the work were prepared scenarios with tasks for the research participants, questionnaires and time of the tasks execution where measured. Collected data were presented as heat maps and scanpaths. The paper covers also actual review of bibliography of the eye-tracking area and detailed description of the eye-tracking method. What is more the paper gives description of test subject, conducted test and discusses results.